Philosophical review of heredity and environment in Islamic education - Firman Mansir; Muhammad Abrar Parinduri; Tumin Tumin; Endro Dwi Hatmanto (Journal of Education and Learning (EduLearn), 2020)
This research explains that heredity affects the formation of personality. However, it is not the only one absolute factor which can’t be changed. In fact, personality can be supple and the tool to change is the environment. The purpose of this study is to show that heredity and environment are important in determining the quality of individual character development in Islamic education studies. In the teachings of Islam, both sourced through the Quran, the Hadith of the Prophet, and the opinions of other experts, although not explicitly stated, there are also several sources that explain and justify that heredity and the environment can affect the growth of character and behavior human behavior. Both heredity and the environment have a very significant relation either individually and together in the education process. Thus, in the world of education a teaching and learning strategy, it is needed to be able to accommodate human and religious values. In other words, humanitarian and religious values are inseparable wither in transfer of knowledge, transfer of value and transfer of method. Therefore the method in this research is uses research type/approach of library research.